Macroeconomics and the Environment: A Selective Survey - Partha Sen (Center for Economic Studies and ifo Institute (CESifo), 2020)
Macroeconomics deals with economics at the aggregate level. This could be at a national level or the interaction between nations. Production of output necessarily involves pollution and degrading the environment. Therefore, environmental issues enter inevitably. Some problems that have been highlighted in the literature are surveyed here. It has been argued that a poor country deliberately lowers its environmental standards that enables it to steal jobs from other countries. What is the theoretical underpinning and the evidence for this assertion? The evidence is very weak in support of this. Also, in the fight against climate change, the poorer countries claim exemption from tightening their emissions norms, because of their poverty. Although equity demands this, it could pose serious challenges to fighting climate change – oil producers would pump oil faster, if they foresee it becoming useless. A piecemeal approach is thus infeasible. A more basic question is how to introduce natural resource use in national income accounts to give meaning to the notion of sustainability? National income accounts do not take into account non-market activities. Some progress has been made in the theory and empirical implementation of sustainability by including non-market activities. A lot of work has been done but a lot more still needs to be done here.
Keywords: Q50; F10; F20; 330; macroeconomics and environment; trade and environment; green paradox; genuine saving; comprehensive wealth